Clinical efficacy, postoperative complication risks, and parental satisfaction in pediatric patients receiving tension-reducing suture treatment for facial lacerations - Mi, Zijing; Zeng, Pingying; Yang, Weiyuan; Sun, Haiyang; Yao, Ping (Frontiers in Pediatrics, 2025)
ObjectiveTo evaluate the clinical efficacy, postoperative complication risks, and parental satisfaction of tension-reducing sutures in pediatric patients with facial lacerations.MethodsA retrospective cohort analysis was conducted on 122 pediatric patients (aged 1–12 years) with facial lacerations who met predefined inclusion criteria (e.g., aged 1–12 years, wound length 1–5 cm, etc.; see Methods for details) and underwent surgical treatment at our hospital between January 2020 and August 2024. Based on the surgical technique received, the patients were divided into the tension-reducing suture group n = 61) and the conventional suture group (n = 61). The two groups were compared regarding baseline clinical characteristics, clinical efficacy, scar formation, surgical features, postoperative complications, and parental satisfaction.ResultsThe primary healing rate (Grade A) in the tension-reducing suture group was 88.5% (54/61), significantly higher than that in the conventional suture group (73.8%, 45/61), with a statistically significant difference (χ2 = 4.340, p = 0.037). At postoperative 1 month [(4.25 ± 1.16) vs. (4.80 ± 1.21)] and 3 months [(3.69 ± 1.03) vs. (4.08 ± 1.10)], the Vancouver Scar Scale (VSS) scores in the tension-reducing suture group were significantly lower than those in the conventional suture group (t = −2.594, −2.044; p = 0.011, 0.043). The tension-reducing suture group had longer operative time [(55.08 ± 11.23) min vs. (50.16 ± 10.46) min], more suture layers [(2.85 ± 0.54) vs. (2.61 ± 0.58)], and more sutures [(41.48 ± 8.42) vs. (38.49 ± 6.20)] compared to the conventional suture group (t = 2.502, 2.406, 2.229; p = 0.014, 0.018, 0.028). No significant difference was observed in intraoperative blood loss between the two groups (p > 0.05). The postoperative complication rate was 4.9% (3/61) in the tension-reducing suture group and 14.8% (9/61) in the conventional suture group, with no statistically significant difference (χ2 = 3.327, p = 0.068). Parental overall satisfaction was 93.4% (57/61) in the tension-reducing suture group and 80.3% (49/61) in the conventional suture group, showing a statistically significant difference (χ2 = 4.604, p = 0.032).ConclusionTension-reducing suture technique is more conducive to promoting primary wound healing and reducing scar formation in pediatric patients. Additionally, this suturing method was associated with a trend towards fewer complications while improving parental satisfaction with surgical outcomes.